Measuring image sharpness using modulation transfer function in magnetic resonance imaging - Taek Lim, Woo; Jeong Kim, Ki; Hee Hong, Dong; Hwan Lim, Cheong; Ryang Jung, Hong (International Journal of Engineering and Technology, 2018)
Background/Objectives: The purpose of this study was to propose a method to maintain the objectivity and validity of measuring image sharpness by changes of ETL using MTF in MRI quantitatively and provide fundamental data for future evaluation and management of magnetic resource imaging quality.Methods/Statistical analysis: We conducted phantom test using ACR MRI phantom. ImageJ and OriginPro programs were used for MTF measurement. For MTF measurement using edge method, after achieving ESF by using ImageJ, LSF was calculated by differentiation in OriginPro. Finally, MTF value was obtained through conversion. Image sharpness was defined based on 50% of MTF value.Findings: Results of sharpness measurement by ETL increase revealed that MTF 50% was decreased when ETL was increased. Sharpness comparison between 1ch head coil and 8ch brain coil at 1.5T showed that it was higher for 1ch head coil, although the difference between the two was not statistically significant. However, sharpness of 1ch head coil at 3.0T MRI was found to be significantly higher than that of 8ch brain coil at 3.0T MRI.Improvements/Applications: This study confirms the theoretical concept that MTF measured by ACR standard phantom can be used as a quantitative evaluation method for spatial resolution in the magnetic resonance medical image quality management. It can be considered a meaningful objective evaluation method.Â Â